2021
DOI: 10.29313/gmhc.v9i1.6409
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Strawberry, Rome Beauty Apple, and New Combination on Fasting Blood as Supporting Diet Therapy in Patients with Type II Diabetes Mellitus

Abstract: Strawberries (Fragaria x ananassa) and Rome beauty apples (Malus sylvestris) contain high antioxidants to reduce oxidative stress and improve the glycemic response with diabetes mellitus (DM) type II. This study aimed to analyze the effect of strawberries, Rome beauty apples, and their combination to decrease fasting blood glucose levels of type II DM patients. This experimental research used a randomized pre-post-test with a control group design. Subjects were 44 patients divided into four groups: K (control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
2
2
0
1
Order By: Relevance
“…Additionally, the literature suggests that a decrease in hyperglycemia level reduced the risk of cardiovascular complications and our results found that strawberry extract affected these parameters in rats. Our results are also in agreement with [15], in which they found the effect of strawberry on diabetic patients, and their data…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, the literature suggests that a decrease in hyperglycemia level reduced the risk of cardiovascular complications and our results found that strawberry extract affected these parameters in rats. Our results are also in agreement with [15], in which they found the effect of strawberry on diabetic patients, and their data…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, the literature suggests that a decrease in hyperglycemia level reduced the risk of cardiovascular complications and our results found that strawberry extract affected these parameters in rats. Our results are also in agreement with [15], in which they found the effect of strawberry on diabetic patients, and their data showed that blood glucose levels decreased from 172.09 ± 28.648 to 141.00 ± 38.079 after 14 days of strawberry (200 g/person/day) consumption. A similar result was also reported by [16], in which they explained that in vitro aqueous extracts of strawberry fruits inhibited enzyme (α-amylase and α-glucosidase) activities that control blood sugar levels.…”
Section: Discussionsupporting
confidence: 93%
“…In the second study, the participants with normal glucose levels received a single apple or pear preload combined with specialised carbohydrate meals. Finally, the fasting blood glucose levels were significantly reduced in diabetes mellitus type II patients who consumed Malus sylvestris fruits for 14 days [150].…”
Section: Human Studiesmentioning
confidence: 90%
“…Flavonoids are important content of strawberry that plays a role in control of diabetes. This is done by inhibition of glucose uptake and helps in maintenance of blood-sugar levels (Yuliwati and Nugroho, 2021;Casto et al, 2013).…”
Section: Potential Use Of Strawberries For Diabetesmentioning
confidence: 99%